International Financial Statistics, January 2019. (International Financial Statistics; International Financial Statistics ;, 2019)
This January 2019 monthly issue of International Financial Statistics (IFS) contains country tables for most IMF members, as well as for Anguilla, Aruba, the Central African Economic and Monetary Community, Curacao, the currency union of Curacao and Sint Maarten, the Eastern Caribbean Currency Union, the euro area, Montserrat, the former Netherlands Antilles, Sint Maarten, the West African Economic Monetary Union, West Bank and Gaza, and some non-sovereign territorial entities for which statistics are provided internationally on a separate basis. Exchange rates in IFS are classified into three broad categories, reflecting the role of the authorities in determining the rates and/or the multiplicity of the exchange rates in a country. The three categories are the market rate, describing an exchange rate determined largely by market forces; the official rate, describing an exchange rate determined by the authorities-sometimes in a flexible manner; and the principal, secondary, or tertiary rate, for countries maintaining multiple exchange arrangements.